The civil engineer's pocket-book - Trautwine, John C. 1810-1883 (Trautwine ; Chapman & Hall, 1922)
This title provides a fundamental guide to civil engineering principles as applied to railway construction, and includes sections on: mathematics, natural phenomena, mechanics, strength of materials, hydrostatics, hydraulics, constructions, water supply, test and well boring, rock drills, traction and animal power, trusses, suspension bridges, rivets and riveting, railroads, materials, and concrete.